Observation of Zigzag-Shaped Magnetic Domain Boundaries in Granular Perpendicular Magnetic Recording Media Using Alternating Magnetic Force Microscopy - M. V. Makarova; Hanamichi Tanaka; Hiroshi Sonobe; Toru Matsumura; Hitoshi Saito (Magnetochemistry)
In granular media for perpendicular magnetic recording, zigzag-shaped magnetic domain boundaries form between magnetic grains isolated by a non-magnetic grain boundary phase. They are the main source of jitter noise caused by the position fluctuation of magnetic bit transitions. The imaging of zigzag boundaries thus becomes an important task to increase recording density with decreasing bit size, when the zigzag and bit sizes become comparable. We visualized the zigzag boundaries of magnetic domains in as-sputtered granular media with a spatial resolution of less than 3 nm using our developed Alternating Magnetic Force Microscopy (A-MFM). We used a soft magnetic amorphous FeCoB tip with high saturation magnetization, which further enhances the spatial resolution through the inverse magnetostrictive effect. The zigzag size ranged from 2 to 8 nm in media with an estimated grain size of around 5 nm. Additionally, we observed zigzag bit boundaries in commercially recorded granular media with a recording density of 500 kfci.